Dispersion and component analysis of the influence of genotype on the formation of performance traits in fattening pigs - Lenkov, Leonid; Леньков, Леонід; Koroban, Marina; Коробань, Марина; Lykhach, Vadym; Лихач, Вадим; Lykhach, Anna; Лихач, Анна; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; et al. (Національний університет біоресурсів і природокористування України, 2025)
The relevance of the work was determined by the need to find effective genetic combinations to increase productivity and ensure the stability of growth processes in animals of modern “commercial genotypes”. The aim of the study was to determine the role of genotype as a determining factor in the growth and development of pigs using one-factor dispersion analysis and principal component analysis. The experiment involved 120 fattening pigs, and the test animals were divided into three groups. Group I: a combination of Large White and Landrace sows with Duroc boars of Canadian selection (Genesus) Group II: a combination of Large White and Landrace sows with Pietrain boars of French selection (Axiom) and Group III: a combination of Large White and Landrace sows with boars of the terminal line “Maxter” selected by the company “France Hybrides”. The assessment was based on the live weight of pigs of different genotypes at the age of 77-203 days, absolute and average daily gains in separate age periods, as well as the age at which they reached a pre-slaughter live weight of 80, 100, 120 and 140 kg. The results of the variance analysis showed a significant influence of genotype on all studied indicators. The greatest effect of the “genotype” factor was observed for live weight at 154 days of age (43.27%), absolute and average daily gains in the period from 182 to 203 days (44.97%), as well as the age at which live weight of 100 kg was reached (44.72%). It was confirmed that pigs in group I were inferior to their peers in other groups in the early stages of life, but in the later stages of fattening, they demonstrated a significant advantage in terms of gains and growth intensity. Animals in groups II and III were characterised by similar growth rates and did not differ statistically significantly from each other. Principal component analysis allowed to identify two stages in the process of live weight formation: the first (130-155 days) and the second (180-205 days), which are determined by different growth mechanisms and are practically independent of each other. The results confirm the key role of genotype in the formation of productive traits in pigs and can be used in the development of breeding programmes and the improvement of fattening systems. Актуальність роботи зумовлена необхідністю пошуку ефективних генетичних поєднань для підвищення продуктивності та забезпечення стабільності ростових процесів у тварин сучасних «комерційних генотипів». Метою дослідження було з’ясування ролі генотипу, як визначального чинника росту та розвитку свиней за допомогою однофакторного дисперсійного аналізу й аналізу головних компонент. В експерименті було використано 120 голів свиней на відгодівлі, піддослідний молодняк був розділений на три групи. І група: поєднання свиноматок великої білої та ландрас з кнурами породи дюрок канадської селекції (Genesus), ІІ група: поєднання свиноматок великої білої та ландрас з кнурами породи п’єтрен французької селекції (Axiom) і ІІІ група: поєднання свиноматок великої білої та ландрас з кнурами термінальної лінії «Maxter» селекції компанії «France Hybrides». Для оцінки використано живу масу свиней різних генотипів у віці 77-203 доби, абсолютні та середньодобові прирости в окремі вікові періоди, а також вік досягнення ними передзабійної живої маси 80, 100, 120 та 140 кг. За результатами дисперсійного аналізу встановлено достовірний вплив генотипу на всі досліджувані показники. Найбільший ефект фактору «генотип» відмічено для живої маси у віці 154 діб (43,27 %), абсолютних та середньодобових приростів у період 182-203 доби (44,97 %), а також віку досягнення живої маси 100 кг (44,72 %). Підтверджено, що свині І групи у ранні вікові періоди поступалися ровесникам інших груп, однак на пізніших етапах відгодівлі демонстрували достовірну перевагу за приростами та інтенсивністю росту. Тварини ІІ та ІІІ груп характеризувалися подібними темпами росту та не відрізнялися статистично значущо між собою. Аналіз головних компонент дозволив виділити два етапи у процесі формування живої маси: перший (130-155 діб) та другий (180-205 діб), які визначаються різними механізмами росту та практично незалежні один від одного. Отримані результати підтверджують ключову роль генотипу у формуванні продуктивних ознак свиней та можуть бути використані при розробці селекційних програм і вдосконаленні систем відгодівлі.
Дисперсійний та компонентний аналіз впливу генотипу на формування продуктивних ознак відгодівельних свиней
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: principal components; головні компоненти; breeding; селекція; breed composition; породність; live weight; жива маса; gains; прирости